2022
DOI: 10.3390/jcm11061568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on Physical Activity and Sedentary Behavior in Older Adults

Abstract: Whether the COVID-19 pandemic has long-lasting effects on physical activity (PA) and sedentary behavior in the vulnerable older adult population is uncertain. A total of 387 older adults (75 ± 6 years) completed a retrospective questionnaire on time spent sitting, walking, and performing aerobic and muscle-strengthening PA before, during the first three months, and one year into the COVID-19 pandemic. Whether the participants met the aerobic and muscle-strengthening PA guidelines was then determined. Of the 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Finally, the data were collected ten years ago. Important events or changes, such as the Covid-19 pandemic, might have affected older adults’ lifestyles [ 56 ]. As such, the variability in sedentary behavior may differ for the current cohort of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the data were collected ten years ago. Important events or changes, such as the Covid-19 pandemic, might have affected older adults’ lifestyles [ 56 ]. As such, the variability in sedentary behavior may differ for the current cohort of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…That is, overweight or obese individuals experienced greater increases in sitting time compared to their normal weight counterparts, and those individuals who met the PA guidelines prior to the pandemic had larger reductions in both aerobic and muscle-strengthening PA during the pandemic. 53 While the exact source for the return of PA and sedentary time one-year after the pandemic is uncertain and likely multifactorial, these findings optimistically suggest that pandemic-related impacts on activity levels is not long-lasting and in fact reversible among populations who are highly prone to have severe COVID-19 outcomes. 4 , 57 Additional efforts should therefore be placed to highlight the importance of PA and longitudinal studies are needed to examine the effects of physical inactivity and SB on health.…”
Section: How the Covid-19 Pandemic Has Affected Pa And Sbmentioning
confidence: 95%
“…A recent retrospective study examined effects of PA and SB among 387 older adults (aged 75 ± 6 years) during the pandemic. 53 Before COVID-19, 67.9%, 61.9%, and 48.9% of older adults met the aerobic, muscle-strengthening, and both PA guidelines, respectively. During the first 3 months of the pandemic (March–May 2020) the percentage of older adults meeting aerobic, muscle-strengthening, or both PA guidelines significantly decreased to 54.8% (−13.1%), 46.1% (−15.8%), and 33.5% (−15.4%), respectively, with a concomitant increase in sedentary time by 7.4 ± 3.1 h/day.…”
Section: How the Covid-19 Pandemic Has Affected Pa And Sbmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and colleagues [10] also reported that a 2-month lockdown in Singapore increased depressive symptoms and decreased physical activity among older people, but more targeted interventions would mitigate the negative impacts of the future lockdown. There has been an increase in studies related to understanding older adults' physical activity experiences and behaviours during the COVID-19 pandemic [e.g., [11][12][13]. For instance, public health guidance published in 2021 by the National Institute for Health and Care Excellence (NICE) in the UK suggests that digital and mobile health interventions could be an effective health tool for supporting community-dwelling older people physically active [14] or videos can be an effective tool for older adults to cope with stress and stay physically active [15].…”
Section: Introductionmentioning
confidence: 99%